Adaptation to the driving simulator and prediction of the braking time performance, with and without distraction, in older adults and middle-aged adults (Clinics, 2023)
Context: Many studies show the importance of evaluating the adaptation time of subjects in a virtual driving environment, looking forwards to a response as closest as a possible real vehicle.ObjectivesThis study aimed to identify and analyze the adaptation to the driving simulator in older adults and middle-aged adults with and without a distraction, and a secondary aim was to identify predictors of safe performance for older adults' drives.Design: Male and female middle-aged adults (n = 62, age = 30.3 ± 7.1 years) and older adults (n = 102, age = 70.4 ± 5.8 years) were evaluated for braking time performance in a driving simulator; cognition performance assessment included the Mini-Mental State Examination; motor evaluation included ankle flexor muscle strength with the isokinetic dynamometer and handgrip strength; the postural balance was evaluated with Timed Up and Go test, with and without a cognitive distraction task.Results: Older adults (men and women) and middle-aged adult women require more time to adapt to the driving simulator. The distractor increases the adaptation time for all groups. The main predictors of braking time for older women are age, muscle strength, and postural balance associated with distraction, and for older men, muscle strength.Conclusions: Age, sex, and distractor interfere in the adaptation of the virtual task of driving in a simulator. The evaluation model developed with multi-domains demonstrated the ability to predict which skills are related to braking time with and without the presence of the distractor.